1688a Office lighting surveys – refocussing on the eye and health. (24th April 2018) - Pisaniello, Dino; Gaskin, Sharyn; D'Orso, Marco; Piccoli, Bruno
Abstract : Introduction: Current guidance on office lighting tends to be oriented towards illumination engineering, i.e. achieving a certain lighting environment. The selection of lamps and luminaires from a vast array of current lighting options, as well as their layout, often reflects architectural style and energy efficiency, rather than 'healthy' lighting – which aims to eliminate or minimise adverse health effects, including visual discomfort, arising from visual tasks and ambient light sources. Methods: Firstly, this paper explores the criteria for healthy lighting based on visual anatomy and pathophysiology and characteristics of workers and tasks in office environments. Secondly, survey methods addressing characteristics of light entering the eye are reviewed in the context of outcomes ranging from discomfort to retinal degradation. Results: A primary consideration is characterisation of light sources in the occupational visual field, (OVF) which is mainly determined by the visual tasks. Another consideration is how, and for how long, the source(s) are imaged on the retina (especially the macula). Again this depends on the visual requirements of the task. Indeed, directionality is much more important for lighting than other hazards such as noise. Such assessments are not possible with an integrating light measuring instrument such as a lux metre. Finally, in the cases of blue-rich sources, the assessment should be more about radiometry than photometry. Discussion: A variety of visual, circadian rhythm and psychological disturbances may arise from inappropriate lighting. The concept of 'healthy' lighting serves to integrate the issues, and surveys of lighting should begin with the OVF and systematic consideration of light sources therein. Assessment should involve luminance and where necessary radiance.